Relación entre el rendimiento y la forma de la panoja en la quinua - Gandarillas Santa Cruz, H; Espindola Pinedo, G. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Quinua's panicle shape, which could be glomerulated or amarantiform, does not relate to yield neither to other yield components such as earliness, height of plant, panicle length and grain diameter.